Profil Keterampilan Proses Sains Mahasiswa pada Mata Kuliah Media Laboratorium Melalui Metode Pembelajaran Demonstrasi - Safnowandi, Safnowandi; Efendi, Ismail (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Biology as a branch of science is a process and a product. The process referred to here is the process through scientific work, while the products are concepts, principles, principles, theories and laws. Laboratory media is a course that is closely related to these activities. This course is worth 3 credits, with details of 2 credits of face-to-face in class and 1 credit of practicum in the Laboratory. So far, lecturers have never identified all indicators of science process skills that appear during laboratory media practicum activities. Assessment of reports and students' scientific work skills has been carried out, but has not been equipped with relevant assessment instruments, so that the science process skills that students already have have not been properly identified. This study aims to determine students' science process skills in laboratory media courses through demonstration learning methods. This study is a type of pre-experimental research, with a research design using the one-shot case study design. The subjects in this study were students of the Biology Education Study Program, Faculty of Science, Engineering, and Applied Sciences, Mandalika University of Education who programmed laboratory media courses in the even semester of the 2023/2024 academic year. The type of data collected is science process skills data and student responses. The instruments used are for science process skills observation sheets and science process skills tests, while for student response data using questionnaires. Data analysis uses quantitative descriptive. The results of this study by calculating the observation sheets of students' science process skills, the data obtained are in the form of several categories of science process skills, including 23 students have a percentage of achievement of science process skills, with the category Very good (15.86%), as many as 39 students are in the category Good (26,90%), as many as 72 students have the category Enough (48,96%), and as many as 12 students have the category less (8,27%).